An Analysis of the Springback Phenomenon of the Material Aluminum Alloy 6063-T5 With Punch Angle Variation - Amri Abdulah; Revi Kusnadi; Mohamad Rizkiyanto; Sukarman; Amir Amir; Dibyo Setiawan (Jurnal Teknik Mesin Mechanical Xplore, 2022)
Springback is a phenomenon that frequently occurs in bending processes and is detrimental to the manufacturing industry. Typical disadvantages include the incompatibility of the product's final dimensions and the need for additional processing. Indeed, these must also incur additional expenses and result in the inefficient production process flow. Consequently, the analysis of springback is attracted to studies to obtain a bending product that meets expectations. This study examined the springback phenomena on 60 mm x 19 mm x 2 mm aluminium alloy 6063-T5 materials using V-bending processes and approximately 40°, 50°, and 60° punch angles. This study also utilized the die opening and bending force variables, 35 mm and 2500 N, respectively. It was anticipated that these procedures would produce a 6063-T5 aluminium alloy with a bending angle of approximately 90 degrees. The results indicate that the bending angles produced by these processes with the various punch angles are 91.50°, 91.42°, and 91.67°, respectively. It indicates that the excess bending angle was referred to as springback. Consequently, a bending angle of approximately 90° can be obtained on aluminium alloy 6063-T5 using V-bending processes with the set parameters of die opening in 35 mm and bending force in 2500 N, in addition to the punch angle that was reduced based on the known springback value. In addition, it is anticipated that this result will contribute to the development of the manufacturing industry, particularly the aluminium alloy 6063-T5 materials industry, or serve as a reference for other relevant studies